2013
DOI: 10.1371/journal.pone.0056394
|View full text |Cite
|
Sign up to set email alerts
|

Within-Plant Bottom-Up Effects Mediate Non-Consumptive Impacts of Top-Down Control of Soybean Aphids

Abstract: There is increasing evidence that top-down controls have strong non-consumptive effects on herbivore populations. However, little is known about how these non-consumptive effects relate to bottom-up influences. Using a series of field trials, we tested how changes in top-down and bottom-up controls at the within-plant scale interact to increase herbivore suppression. In the first experiment, we manipulated access of natural populations of predators (primarily lady beetles) to controlled numbers of A. glycines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…In the presence of predators, the aphid's spatial distribution significantly shifted towards the lower leaves of the plants. Because coccinellids tend to forage more often and longer on the plant's upper parts (Costamagna & Landis, ; Hodek & Honĕk, ), we attribute this spatial distribution shift to a predator avoidance behaviour that, as reported in previous studies, reduces predation risk at the cost of feeding on lower‐quality plant tissues (Costamagna & Landis, ; Costamagna et al., ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the presence of predators, the aphid's spatial distribution significantly shifted towards the lower leaves of the plants. Because coccinellids tend to forage more often and longer on the plant's upper parts (Costamagna & Landis, ; Hodek & Honĕk, ), we attribute this spatial distribution shift to a predator avoidance behaviour that, as reported in previous studies, reduces predation risk at the cost of feeding on lower‐quality plant tissues (Costamagna & Landis, ; Costamagna et al., ).…”
Section: Discussionmentioning
confidence: 71%
“…This reduces the immediate predation risk at a cost of garnering resources in suboptimal environments (Downes, ; Lima, ; Sih, Englund, & Wooster, ). Here, we found that, in the absence of ladybeetles, aphids typically stay at the plant's apex, which is their preferred feeding site due to the high nutritional quality of vigorously growing apical tissues (Cibils‐Stewart, Sandercock, & McCornack, ; Cornelissen, Wilson Fernandes, & Vasconcellos‐Neto, ; Costamagna, McCornack, & Ragsdale, ; Dixon, ). In the presence of predators, the aphid's spatial distribution significantly shifted towards the lower leaves of the plants.…”
Section: Discussionmentioning
confidence: 97%
“…Aphis glycines performance is positively correlated with G. max N content (Myers et al., ; Myers & Gratton, ; Walter & DiFonzo, ), which is highest in the top nodes (Muchow et al., ; Shiraiwa & Sinclair, ). Although the within‐plant distribution of A. glycines changes throughout the season, most individuals in a colony are typically found feeding on the top nodes of G. max (Wu et al., ; McCornack et al., ; Costamagna & Landis, ; Costamagna et al., ). Thus, the within‐plant spatial distribution of A. glycines likely constitutes a behavioral adaptation to within‐plant quality variation, as is observed in other aphid species (Dixon, ; Straw et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, unifoliate leaves of G. max plants grown under laboratory conditions were excised and placed on moist paper towel circles kept inside plastic Petri dishes (1 cm high, 9 cm diameter; Fisherbrand, Ottawa, ON, Canada). Young G. max leaves were used due to their high nutritional quality, demonstrated by A. glycines aggregations on newly developed plant tissue (McCornack et al., ; Costamagna et al., ). Adult apterous aphids were haphazardly selected from the laboratory colony and placed in groups of three on the excised leaves, where they were allowed to reproduce for 24 h before being removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation